2009
DOI: 10.1128/iai.01164-08
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Differences in Salivary Pathogen Load during Tick Transmission Underlie Strain-Specific Variation in Transmission Efficiency ofAnaplasma marginale

Abstract: The relative fitness of arthropod-borne pathogens within the vector can be a major determinant of pathogen prevalence within the mammalian host population. Strains of the tick-borne rickettsia Anaplasma marginale differ markedly in transmission efficiency, with a consequent impact on pathogen strain structure. We have identified two A. marginale strains with significant differences in the transmission phenotype that is effected following infection of the salivary gland. We have proposed competing hypotheses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 30 publications
3
63
0
Order By: Relevance
“…Although I. scapularis hemolymph is poorly borreliacidal (76), elimination of spirochetes by cellular innate defenses within the hemocoel, shown herein by us and others (15), may further limit the number of organisms that reach their salivary gland target. Because salivary glands are a well-recognized anatomical barrier for vector-borne pathogens (6,(77)(78)(79), it is also plausible that this organ impedes the migration of B. burgdorferi. Along these lines, our visualization of spirochetes in association with the acinar surface as well as with multiple intraglandular structures raises the possibility that, as postulated for the midgut, the salivary glands comprise a succession of obstacles that the spirochete must negotiate via a multistep process in order to attain its goal of accessing the salivary stream.…”
Section: Figurementioning
confidence: 99%
“…Although I. scapularis hemolymph is poorly borreliacidal (76), elimination of spirochetes by cellular innate defenses within the hemocoel, shown herein by us and others (15), may further limit the number of organisms that reach their salivary gland target. Because salivary glands are a well-recognized anatomical barrier for vector-borne pathogens (6,(77)(78)(79), it is also plausible that this organ impedes the migration of B. burgdorferi. Along these lines, our visualization of spirochetes in association with the acinar surface as well as with multiple intraglandular structures raises the possibility that, as postulated for the midgut, the salivary glands comprise a succession of obstacles that the spirochete must negotiate via a multistep process in order to attain its goal of accessing the salivary stream.…”
Section: Figurementioning
confidence: 99%
“…The numbers of organisms in the salivary gland and saliva at the time of transmission are 10-fold and 30-fold less, respectively, than the numbers of organisms in a high-transmission-efficiency strain (25). Transmission is correspondingly less efficient and requires Ͼ30-fold more ticks (9,25). This statistically and biologically significant transmission phenotype provides a model for linking gene content and expression with transmission efficiency.…”
mentioning
confidence: 99%
“…For example, cholera pandemics are associated with a limited diversity of related, highly transmissible Vibrio cholerae strains (4). For vectorborne pathogens, efficient transmission is also dictated by infection and replication within the arthropod host (10,15,25,26). While the basic cycle of development within the arthropod vector has been identified for many important pathogens, including Anaplasma, Borrelia, Plasmodium, Rickettsia, and Trypanosoma, the critical microbial determinants of transmission efficiency in the vector remain unknown for most bacterial and protozoan pathogens.…”
mentioning
confidence: 99%
“…centrale vaccine strain was thought for a long time not to be transmitted by most ticks, it was shown that, in fact, it colonized the tick well but was not secreted into the tick saliva in sufficient quantities for robust transmission (23,24). Dramatically increasing tick numbers in transmission experiments overcame the transmission barrier (25). Is the reduced ability of the A. marginale subsp.…”
Section: Discussionmentioning
confidence: 99%